Evaluation of Association between PPARGC1A Gene Polymorphism and Competitive Performance of Elite Athletes - ULUCAN, KORKUT (My University, 2022)
PPARGC1A (rs8192678) gen polimorfizmi ve atletik performans arasıdaki ilişkiler konusunda sınırlı sayıda araştırma mevcuttur. Bu nedenle, bu çalışmada PPARGC1A genindeki rs8192678 polimorfizminin Türk elit atletizm sporcularının yarışma performansları ile olası ilişkisin araştırılması amaçlamaktadır. Çalışmaya 18-35 yaşları arasında toplam 60 elit sporcu (31 sprint/güç ve 29 dayanıklılık) ve 20 kontrol/sedanter gönüllü olarak katıldı. Atletlerin kişisel en iyi (PB)/yarışma performans düzeylerini belirlemek için Uluslararası Atletizm Federasyonları Birliği (IAAF) puan ölçeği kullanıldı. Tüm ekzom dizilimi (WES), katılımcıların kanından izole edilen genomik DNA tarafından gerçekleştirildi. rs8192678 polimorfizmi ile PB arasındaki ilişki, cinsiyet ve spor deneyimi ayarlaması ile tek yönlü kovaryans analizi (ANCOVA) ile incelendi. Bulgulara göre grup içi ve gruplar arasında, G/G, G/A ve A/A genotip dağılımları arasında anlamlı bir farklılık tespit edilmemiştir (p>0.05). Sonuç olarak, PPARGC1A rs8192678 polimorfizmi ile sporcuların performansı arasında anlamlı hiçbir ilişki tespit edilmemiştir. Ancak, yapılan araştırma hakkında daha net bilgi verebilmek için daha fazla katılımcı ile yapılması önerilir.

Limited number of researches exist on the relationship between PPARGC1A gene polymorphism (rs8192678) and affects the athletic performance. Thus, the present study aims to decipher any possible association of the rs8192678 polymorphism in the PPARGC1A gene with the competitive performances of Turkish elite track and field athletes. A total of 60 elite athletes (31 sprint/power and 29 endurance) and 20 control/sedentary with the ages of 18-35 voluntarily participated in the study. The International Association of Athletics Federations (IAAF) score scale was used to determine the performance levels of the personal best (PB) of the athletes. Whole exome sequencing (WES) was performed by the genomic DNA sample isolated from blood of the participants. The association between rs8192678 polymorphism and PB was examined by one-way analysis of covariance (ANCOVA) with the adjustment of sex and sport experience. According to the results, there were not any significant deviation between the wild-type (G/G), heterozygote (G/A) and homozygote (A/A) genotypes within and between the groups (p>0.05). Our results underlined that there were not any significances for association of rs8192678 polymorphism with PBs within the groups of the sprint/power and endurance athletes. However, it is recommended that similar studies be conducted with more participants to provide clearer information about the research.
PPARGC1A Gen Polimorfizmi (rs8192678) ile Elit Sporcuların Yarışma Performansları Arasındaki İlişkinin Değerlendirilmesi
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Athletics; Sprint; Power; Endurance; PPARGC1A; Polymorphism; rs8192678; Atletizm; Sürat; Güç; Dayanıklılık; Polimorfizm